THE EFFECTIVENESS OF USING CUE CARD MEDIA TO REDUCE STUDENT’S SPEAKING ANXIETY AT SECOND GRADE STUDENT OF SMKN 1 MATARAM - Sudirman; Tawali, Tawali (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research was aimed at find out the effectiveness of using Cue Card Media toward student’s speaking anxiety in learning English speaking. This research was an experimental research. The population this was the second grade students of SMKN 1 Mataram in academic year 2022/2023 were 218 students. The sample of the research were 64 students. Akl 1 as experimental group and Akl 2 as control group. The sample technique used in this was cluster random sampling technique.The instrument that was used Speaking test namely Describing Object The score were analyzed by used descriptive and inferential analysis. Descriptive analysis was used to describe mean, mode, median, and standard deviation of group according to Anas Sudijono:2007, and inferential analysis was used to describe the value of t-test for comparison between t-table. It was showed that the value of-test = 7.164 was higher than the value of t-table = 1.998. So, using Cue Card Media approach has positive effect toward student’s speaking anxiety in learning English at SMKN 1 Mataram.